A model for making decisions about ethical dilemmas in student assessment. Issue 2 (3rd April 2017) - Johnson, Robert L.; Liu, Jin; Burgess, Yin
Abstract: In this mixed-methods study we investigated the development of a generalized ethics decision-making model that can be applied in considering ethical dilemmas related to student assessment. For the study, we developed five scenarios that describe ethical dilemmas associated with student assessment. Survey participants (i.e., educators) completed an online survey to express their decision-making process when faced with ethical dilemmas relating to student assessment. Based on the literature and the educators' written responses to the scenarios, elements to consider in an ethics decision-making model related to student assessment include the following: (1) the critical incident giving rise to the ethical dilemma; (2) identification of the conflict elements; (3) decisions about the ethicality of the elements; (4) justification of the decisions; (5) implications; and (6) alternative suggestions. This model offers guidance to educators in considering the dimensions of an ethical dilemma in assessment prior to making a decision.